THE INFLUENCE OF TIME MOTION STUDY IMPLEMENTATION ON THE DETERMINATION OF PRODUCTION NET PRICE (ACASE STUDY OF WOODEN FURNITURE MANUFACTURER IN PRODUCTION DEPARTMENT OF PT.CEGE ONE SEMARANG) - Noviati Aning RizkiMustikaSari; Lusia M Silitonga; Sri Marhaeni Salsiyah (JOBS (Jurnal Of Business Studies), 2017)
Production net price of manufacturing product determination is affected by many factors. This research analyzes the influence of Time Motion Study implementation on the determination of production net price in production department of PT. CEGE ONE Semarang. SEM (Structural Equation Model) is used in analyzing this research. Technique of collecting data in this research is interview, observation, and documentary study. The primary data used in this research is the output of Time Motion Study implementation, whereas the secondary data used in this research is material cost, labor cost, overhead cost, and production net price of wooden furniture products. The amount of sample is 101 units of wooden furniture product which are tagged with Time Motion Study label. The result analysis which is carried out by AMOS shows Time Motion Study implementation is more influentialon Labor Cost. Furthermore, Material Cost is more influential on Production Net Price Determination. Moreover, Time Motion Study implementation effectively and efficientlyaffectsProductionNetPriceDeterminationby49,2%.